Epileptic Encephalopathy With Continuous Spike and Wave During Sleep Associated to Periventricular Leukomalacia. (November 2014) - De Grandis, Elisa; Mancardi, Maria Margherita; Carelli, Valentina; Carpaneto, Manuela; Morana, Giovanni; Prato, Giulia; Mirabelli-Badenier, Marisol; Pinto, Francesca; Veneselli, Edvige; Baglietto, Maria Giuseppina
Periventricular leukomalacia is the most common type of brain injury in premature infants. Our aim is to describe the frequency and the features of epilepsy in a single-center population of 137 children with periventricular leukomalacia. Forty-two of the 137 (31%) patients presented epilepsy. Twelve percent of these patients presented West syndrome, whereas 19% showed a pattern of continuous spike-waves during slow sleep syndrome. In the latter group, outcome was frequently unfavorable, with a greater number of seizures and more drug resistance. A significant association was found between epilepsy and neonatal seizures, spastic tetraplegia, and mental retardation. Although less common than in other forms of brain injury, epilepsy is nevertheless a significant complication in children with periventricular leukomalacia. The fairly frequent association with continuous spike-waves during slow sleep syndrome deserves particular attention: electroencephalographic sleep monitoring is important in order to provide early treatment and prevent further neurologic deterioration.